5 - PROFESSOR ABDALLA SAID BUJRA, (1938–2025) A Pioneer Pan-African Scholar, an Institution-Builder and Man of Conscience - Michael Chege, (CODESRIA Bulletin, 2025)
Professor Abdalla Said Bujra, the Kenyan scholar who passed away on 8 January in Malindi, leaves behind an internationally recognised contribution to the social science disciplines in Africa, his published body of work ranging from social anthropology to an informed his- tory of Eastern Africa’s coast, from the problems of underdevelopment and neocolonialism in Africa to social democracy and governance reforms in contemporary Africa. He was actively involved in the founding and management of Africa’s leading social and economic research centre – the Council for the Development of Economic and Social Science Research in Africa (CODESRIA) in Dakar, Senegal – in the 1970s, as well as the Development Policy Management Forum (DPFM) in Addis Ababa and Nairobi, in the 1990s. He taught at universities in Kenya, Tanzania, Germany and the US, and is widely published. But unlike the windbags and self-appointed ‘professors’ who now saturate the social media and the press, Bujra shunned publicity and was modest to a fault. As a result, many Kenyans may not have heard of him, let alone met him outside his small circle of serious scholars and committed policy analysts.